Expression of three forms of nitric oxide synthase in peripheral nerve regeneration - González-Hernández, Tomás; Rustioni, Aldo (Journal of neuroscience research, 1999)
Nitric oxide (NO) is a short‐lived molecule with messenger and cytotoxic functions in nervous, cardiovascular, and immune systems. Nitric oxide synthase (NOS), the enzyme responsible for NO synthesis, exists in three different forms: the neuronal (nNOS), present in discrete neuronal populations; the endothelial (eNOS), present in vascular endotheliun, and the inducible isoform (iNOS), expressed in various cell types when activated, including macrophages and glial cells. In this study, we have investigated the possible involvement of NO in Wallerian degeneration and the subsequent regeneration occurring after sciatic nerve ligature, using histochemistry and immunocytochemistry for the three NOS isoforms, at different postinjury periods. Two days after lesion, the three NOS isoforms are overexpressed, reaching their greatest expression during the second week. nNOS is upregulated in dorsal root ganglion neurons, centrifugally transported and accumulated in growing axons. eNOS is overexpressed in vasa nervorum of the distal stump and around ligature, and iNOS is induced in recruited macrophages. These findings indicate that different cellular sources contribute to maintain high levels of NO at the lesion site. The parallelism between NOS inductions and well‐known repair phenomena suggests that NO, acting in different ways, may exert a beneficial effect on nerve regeneration. J. Neurosci. Res. 55:198–207, 1999.  © 1999 Wiley‐Liss, Inc.